Peningkatan Kesadaran dan Budaya Keselamatan Pelayaran melalui Edukasi Psikologi Keselamatan pada Awak Kapal Tradisional dan Masyarakat Pesisir di Pelabuhan Tanjung Tembaga - Purwitasari, Diyah; Arleiny Arleiny; Agus Dwi Santoso; Elly Kusumawati (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2026)
This community service program aimed to enhance maritime safety awareness and build a safety culture among coastal communities and traditional vessel crews at Tanjung Tembaga Port and the waters of Gili Ketapang, Probolinggo. Maritime accidents in coastal areas often result from not only technical issues but also human and psychological factors, such as panic and poor risk perception (Hetherington et al., 2006; Reason, 2000). Therefore, the program focused on educating participants about maritime safety psychology as a preventive measure to reduce risks. The activities included socialization, safety counseling, and emergency simulation exercises, conducted in collaboration with the Probolinggo Class IV Harbormaster and Port Authority (KSOP). The program was implemented on August 20, 2025, and involved traditional vessel crews, local residents, and port stakeholders. Evaluation was done through participant satisfaction surveys and qualitative observations. Results showed that 75.40% of participants found the program highly beneficial in enhancing their knowledge, skills, and psychological preparedness for emergencies at sea. Additionally, there was an improvement in participants' ability to manage panic, comprehend emergency communication, and follow maritime safety regulations. The program also fostered stronger collaboration between educational institutions and maritime authorities. Overall, it successfully raised safety awareness and contributed to building a lasting safety culture in coastal communities, serving as a model for other maritime regions in Indonesia.